Are Indonesian Farmers a Good Manager? A study on Entrepreneurial and Marketing Orientation to Farm Business Performance in Indonesia - Novi Haryati (Jurnal Manajemen dan Organisasi, 2021)
Farming is including a business entity because its activities include not only planting on land but also being able to maintain relationships that focus on business interests, such as increased sales and income. As the actor in the business, they are required to be able to have marketing and entrepreneurial skills so that their business performance can be sustainable. The purpose of the research is to understand the relationship between marketing and entrepreneurship to the farming performances, with organization innovation as intervening variables. It is quantitative research and has been conducted in Singosari sub district Malang, Indonesia. Analysis was done by SEM-PLS while 40 farmers were chosen purposively as respondent. The result shows that the Indonesian farmer has basic marketing and entrepreneurship orientation. Both of them has positive and highly significant with the value of 0,41 and 0,53 to farming performance. As an intervening variable, Organizational innovation has positively associated with farmer’s performance. Improving the human resources of farmers has been a very important aspect of sustainable business and human resources itself in Agriculture. An experienced and trained farmer will be able to keep working event in an unstable situation.